Komunitas Burung di Pulau Tidung Kecil Kepulauan Seribu - Paskal Sukandar; Ai Winarsih; Fahma Wijayanti (Al-Kauniyah: Jurnal Biologi, 2015)
Tidung Kecil Island had potential as bird’s habitat because the condition of forest better than Tidung Besar. Bird’s habitat in Tidung Kecil Island also had bad potential because of logging and burned in vegetation areal for build and for activity of tourism. Study about bird were very important because we could know the change that happened in one ecosystem. The purposed of this research was to know the variety of bird and usefully of vegetation as bird’s habitat in Tidung Kecil Island. This researched hold on January until March 2015 in Tidung Kecil Island, Thousand Island, Jakarta. This research carried out by combination of IPA (Index Point Of Abundance) method and transect method that divided into 9 point along transect. The result of researched were 29 species of bird from 19 family with IPA method and 31 species of bird from 20 family with Mackinnon list method. Composition of bird species include of 24 resident bird species and 7 migrant bird species. The number of variety species index was 2,39 (medium). Evenness index value was 0,7 (high). The number of species richness was 4,31(high). The species of tree that often used by bird was Casuarina equisetifolia (76,47%). The most used base of vertical level tree by bird in Tidung Kecil Island was level three. Conservation status in Tidung Kecil Island based on IUCN (International Union for Conservation of Nature and Natural Resources) were 100% (least concern). Based on Government Regulations No.7 year 1999, there were 7 species of bird that were protected. There were no species of bird that were protected by CITES (Convention on International Trade of Endangered Spesies of Wild Fauna and Flora).